2016
DOI: 10.21276/aimdr.2016.2.4.58
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological Study of Palpable Breast Lumps: Spectrum of Lesions and Diagnostic Utility of FNAC

Abstract: Background: Palpable breast lumps are quite common which can be benign or malignant. Carcinoma breast is the second most common cancer after cervical cancer. Fine needle aspiration cytology (FNAC) is a minimally invasive, rapid, reliable and cost-effective outdoor procedure to provide effective diagnosis and way to further planning of treatment without need for biopsy. The objective of the study is to study the spectrum of various breast lesions on cytomorphology and its histopathological correlation. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
(14 reference statements)
4
7
0
Order By: Relevance
“…Discussion FNAC of breast lesions is a simple, easy and cost effective procedure. The majority of the palpable breast lesions occurred in females in third to fourth decade of life which correlated with the study conducted by Chamdanwale et al 11 and Likhar et al 12 In the present study, breast lesions had more preponderance to right side compared to left which is similar to study conducted by Binayke R et al 13 whereas study by Ahmad F et al 8 showed left preponderance.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Discussion FNAC of breast lesions is a simple, easy and cost effective procedure. The majority of the palpable breast lesions occurred in females in third to fourth decade of life which correlated with the study conducted by Chamdanwale et al 11 and Likhar et al 12 In the present study, breast lesions had more preponderance to right side compared to left which is similar to study conducted by Binayke R et al 13 whereas study by Ahmad F et al 8 showed left preponderance.…”
Section: Resultssupporting
confidence: 91%
“…5,6 Breast carcinomas are leading cause of morbidity and mortality in women. 7,8 In Indian, breast carcinoma is the second most common malignancy preceded by cervical carcinoma, comprising 22.2% of all new cancers diagnosis and 17.2% of all cancer deaths. 8 Fine needle aspira tion cytology has become widely accepted as simple, cost effective, diagnostic tool with high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In present study, among the benign lesions, fibroadenoma was the most common benign lesion 60 (48 %) followed by Proliferative breast lesion without atypia inclusive of fibrocystic disease (30 cases; 24.4%), this study is comparable to study by Faiyaz Ahmad [13] (41.07%) followed by proliferative breast lesion without atypia (14.29%) and Neha Kurmi Patel et al, [14] . who reported 43.5% cases of fibroadenoma and 24.1 % cases of Fibrocystic disease.…”
Section: Discussionsupporting
confidence: 80%